First report on Paratischeria from Asia (Lepidoptera: Tischeriidae) - Xu, Jiasheng; Dai, Xiaohua; Liu, Peng; Bai, Haiyan; Diškus, Arūnas; Stonis, Jonas R. (Zootaxa, 2017)
We provide the first report on the leaf-mining Tischeriidae genus Paratischeria Diškus & Stonis from Asia. We describe Paratischeria jingdongensis Xu & Dai, sp. nov., a new species discovered in Yunnan, China, feeding on Dalbergia assamica Benth., Fabaceae and redescribe P. hestias (Meyrick, 1915), comb. nov., a hitherto very little known species from India, which has been recently discovered in northern Vietnam, feeding on Helicteres viscida Blume, Malvaceae. We also report on the Fabaceae family as a novel host-plant family of Tischeriidae. The described and redescribed Paratischeria species are illustrated with photographs of the leaf-mines, adults, genitalia, and habitats. We also provide maps of new Paratischeria findings, and, along with a diagnostic scheme to the genus, present some data on global distribution of Paratischeria occurring in tropical and subtropical regions on both sides of the Equator. In addition, we designate a new Paratischeria neotropicana species group and provide two more new taxonomic combinations: Paratischeria heteroterae (Frey & Boll, 1878) comb. nov. and P. capnota (Meyrick, 1915) comb. nov.